Chimeric antigen receptor-T cells are effective against CEACAM5 expressing non-small cell lung cancer cells resistant to antibody-drug conjugates - Kim, Ye-Jin; Li, Wei; Zhelev, Doncho V.; Mellors, John W.; Dimitrov, Dimiter S.; Baek, Du-San (Frontiers in Oncology, 2023)
Chimeric antigen receptor-T (CAR-T) cells and antibody-drug conjugates (ADCs) are promising therapeutic strategies in oncology. The carcinoembryonic antigen-related cell adhesion molecule 5 (CEACAM5) is overexpressed in tumors including non-small cell lung cancer (NSCLC) and pancreatic ductal adenocarcinoma (PDAC), and is an attractive target for therapies based on CAR-T cell or/and ADCs. We previously developed a highly specific antibody-based CAR-T cells targeting CEACAM5 and the tumoricidal effect of CAR-T cells was proved against neuro-endocrine prostate cancer (NEPC) cells expressing CEACAM5. Here, we compare the anti-tumor efficacy of our CAR-T cells with that of an anti-CEACAM5 ADC being clinically evaluated against NSCLC. Our anti-CEACAM5 CAR-T cells showed cytotoxicity in a CEACAM5 surface concentration dependent manner and reduced tumor growth in both ADC-responsive and -non-responsive CEACAM5-expressing NSCLC cells in vitro and in vivo. In contrast, the ADC exhibited cytotoxicity independent on the CEACAM5 cell surface concentration. Even though clinical translation of CEACAM5 targeting CAR-T cell therapies is still in preclinical stage, our CAR-T cell approach could provide a potential therapeutic strategy for CEACAM5-positive cancer patients with resistance to ADCs.